Central bank transparency under model uncertainty - Stefano Eusepi (Federal Reserve Bank of New York, 2005)
This paper explores the effects of central bank transparency on the performance of optimal inflation targeting rules. I assume that both the central bank and the private sector face uncertainty about the correct model of the economy and have to learn. A transparent central bank can reduce one source of uncertainty for private agents by communicating its policy rule to the public. The paper shows that central bank transparency plays a crucial role in stabilizing the agents' learning process and expectations. By contrast, lack of transparency can lead to expectations-driven fluctuations that have destabilizing effects on the economy, even when the central bank has adopted optimal policies
Keywords: E52; E31; E63; 330; Geldpolitik; Regelgebundene Politik; Inflation Targeting; Lernprozess; Staatliche Information; Theorie